Race and premium misrating in the U.S. Federal Crop Insurance Program - Teal, Jim; Stevens, Andrew W. (Applied Economic Perspectives and Policy, 2024)
USDA farm support programs have an established history of racial discrimination. Today, the Federal Crop Insurance Program is among the largest and most important programs available to U.S. farmers. Previous research has documented systematic misrating of crop insurance premiums with sizable welfare implications. In this paper, we explore whether producer race measured at the county level has explanatory power in a model of crop insurance misrating. We find that in some cases it does, raising concerns about the possibilities of racially discriminatory impacts of the RMA's rate-setting methodology. Further research is needed to isolate the mechanisms that explain our findings.
Keywords: Crop Insurance; Premium Misrating; U.S. Farmers; U.S. Federal Crop Insurance Program; Race